2017
DOI: 10.1016/j.ekir.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thrombotic Microangiopathy on Clinical Outcomes in Indian Patients With Lupus Nephritis

Abstract: IntroductionIn addition to glomerular lesion, renal vascular lesion is also an important prognostic marker of lupus nephritis (LN). Among patients with various vascular changes, individuals with thrombotic microangiopathy (TMA) present with severe clinical manifestations and have a high mortality. The aim of the present study was to assess the spectrum and impact of TMA on the outcomes of LN. In a prospective observational study of 2.5 years’ duration, clinical and renal histopathological data regarding biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…43 Additionally, evidence of thrombotic microangiopathy may be present in 5–25% of patients with LN. Nevertheless, data from observational studies regarding its impact on prognosis are equivocal; six studies have shown association of thrombotic microangiopathy with poor long-term renal outcomes (OR ranging from 2.14 to 5.80) or worse response to treatment, 44– 49 while five studies have failed to show such an association. 5054…”
Section: Resultsmentioning
confidence: 99%
“…43 Additionally, evidence of thrombotic microangiopathy may be present in 5–25% of patients with LN. Nevertheless, data from observational studies regarding its impact on prognosis are equivocal; six studies have shown association of thrombotic microangiopathy with poor long-term renal outcomes (OR ranging from 2.14 to 5.80) or worse response to treatment, 44– 49 while five studies have failed to show such an association. 5054…”
Section: Resultsmentioning
confidence: 99%
“…In our prospective series of 197 patients with LN, 50 (25.4%) patients had evidence of TMA. A total of eight (16%) patients received PLEX.…”
Section: Baseline Characteristics Clinical Presentation Histologicamentioning
confidence: 77%
“…Thrombotic microangiopathy (TMA) is a rare, life‐threatening disease that involves multiple systems by microvascular occlusion. Recent studies have reported a prevalence of TMA in lupus nephritis (LN) around 25% . The increase in incidence may be related to improved understanding of the disease entity.…”
Section: Baseline Characteristics Clinical Presentation Histologicamentioning
confidence: 99%
“…TMA with LN on kidney biopsy may be due to antiphospholipid antibodies/syndrome ([APS], anticardiolipin antibodies, anti-b2 glycoprotein I, and lupus anticoagulant), thrombotic thrombocytopenic purpura, or atypical hemolytic uremic syndrome. 134,135 Treatment should be guided by the underlying etiology of TMA. 134 Plasma exchange is indicated for thrombocytopenic purpura, but it may also be beneficial in cases of refractory APS.…”
Section: Special Circumstancesmentioning
confidence: 99%